Evaporation crystallization of zero-dimensional guanidinium bismuth iodide perovskite single crystal for X-ray detection. Issue 3 (17th December 2021) - Xu, Yaxin; Hu, Jiarui; Xiao, Xingfu; He, Huanfeng; Tong, Guoliang; Chen, Junnian; He, Yunbin
Abstract : We synthesized zero-dimensional (0D) lead-free guanidinium bismuth iodide ((Gua)3 Bi2 I9 ) single crystals via an antisolvent-assisted evaporation crystallization method, and exploited their potential X-ray detection merits. Abstract : Bismuth halide hybrid perovskites have aroused intense interest in optoelectronic fields. However, developing novel bismuth halide hybrid perovskites to balance the hydrophobicity and electron transport ability is still challenging. Besides, the conventional temperature-lowering crystallization method usually causes high supersaturation and facilitates the formation of impurity phase and defect structures. Herein, we reported the synthesis of bulk zero-dimensional (0D) guanidinium bismuth iodide ((Gua)3 Bi2 I9 ) single crystals via an antisolvent-assisted evaporation crystallization method at room temperature. The as-grown (Gua)3 Bi2 I9 single crystals have sizes of up to 5 × 5 × 0.6 mm 3 . Besides, they have shown to have distinct semiconductor properties, such as a direct bandgap of 2.08 eV, low density of defects and traps of 3.35 × 10 10 cm −3 and obvious photoconductivity. Moreover, (Gua)3 Bi2 I9 exhibits a large bulk resistivity of 3.94 × 10 11 Ω cm and strong X-ray attenuation coefficient, which satisfies the distinct attributes for X-ray detection. As a consequence, the assembled vertical Au/(Gua)3 Bi2 I9 single crystal/Au X-ray photoconductor achieves a sensitivity of 18.23 μC Gyair −1 cm −2 at a bias voltage of 500 V. This study provides a new horizon for the design and synthesis of bismuth halide perovskites toward non-toxic X-ray detectors.